Factors Associated with Uptake of Contraceptives among HIV Positive Women on Dolutegravir based Anti-Retroviral Treatment at Health Centres of Kampala Capital City Authority. A cross sectional study in Uganda. - Mbabazi, Leah; Nabaggala, Mariah Sarah; Kiwanuka, Suzanne; Kiguli, Juliet; Okoboi, Stephen; Laker, Eva; Castelnuovo, Barbara; Lamorde, Mohammed; Kiconco, Arthur; Amperiize, Mathius (BMC Women's Health, 2022)
In May 2018, the World Health Organisation issued a teratogenicity alert for HIV positive women using dolutegravir (DTG) and emphasised increased integration of sexual and reproductive services into HIV care to meet contraceptive needs of HIV positive women. However, there are scarce data on the impact of this guidance on contraceptive uptake. Objective To investigate the uptake of contraceptives and the factors affecting the uptake of contraceptive services among the HIV positive women of reproductive age who use DTG. Methods A cross-sectional survey was conducted from April 2019 to July 2019, in five government clinics in central Uganda where DTG was offered as the preferred first-line antiretroviral treatment (ART) regimen. We randomly selected 359 non-pregnant women aged 15-49 years using DTG-based regimens. We used interviewer administered questionnaires to collect data on demographics, contraceptive use, social and health system factors. We defined contraceptive uptake as the proportion of women using any method of contraception divided by the total number of women on DTG during the review period. We described patients’ characteristics using descriptive statistics. Factors associated with contraceptive uptake were investigated using Poisson regression at multivariable analysis (STATA 14). Results Of the 359 participants, the mean age was 37(SD=6.8), half 50.7% had attained primary level of education and average monthly income <100,000Ushs. The overall level of Contraceptive uptake was 38.4%, modern contraceptive uptake was 37.6% and 96.4% of the participants had knowledge of contraceptives. The most utilised method was the injectable at 58.4% followed by condoms 15%, IUD 10.7%, pills 6.4%, implants 5.4%, and least used was sterilization at 0.7%. Predictor factors that increased likelihood of contraceptive uptake were; religion of others category AIRR=1.53(95% CI: 1.01, 2.29) and parity 3-4 children AIRR=1.48(95% CI: 1.14, 1.92). Reduced rates were observed for age 40-49 years AIRR=0.45(95% CI: 0.21, 0.94), unemployment AIRR 0.63(95% CI: 0.42, 0.94), not discussing FP with partner AIRR=0.39(95% CI: 0.29, 0.52) and not receiving FP counselling AIRR=2.86 (95% CI: 0.12, 0.73). Non-significant variables were facility, education level, marital status, sexual activity, experienced side effects of FP and knowledge on both contraceptives and DTG. Conclusion This study shows a low-level uptake of contraceptives and injectable was the most used method. It also indicated that FP counselling and partner discussion on FP increased contraceptive uptake. Therefore, more strategies should be put in place to increase male involvement in family planning programs and scale up the integration of family planning services into HIV care and management programs.
Keywords: Contraceptives; Anti-Retroviral Treatment; Dolutegravir